Hubungan Rasa Syukur terhadap Tingkat Stress Dewasa Awal - Friskha Hapsari; Rahmadianti Aulia (CV. ITTC INDONESIA, 2026)
This study explores the impact of gratitude on stress levels among young adults, emphasizing its relevance within Islamic psychology. Young adulthood, a period characterized by numerous challenges and pressures, is particularly susceptible to stress. Utilizing a qualitative descriptive approach, this literature review analyzed eight relevant studies. The findings consistently indicate that higher levels of gratitude correlate with lower stress levels, acting as a protective factor. For instance, research by Salim and Qurotul Uyun (2023) demonstrated a significant negative correlation between gratitude and psychological distress among final-year students. Additionally, gratitude serves as a moderator between stress and well-being, enhancing psychological resilience. Interventions such as Al-Ghazali's gratitude training effectively reduce stress in diverse populations, including healthcare workers and students. This research underscores the importance of integrating gratitude into psychological interventions to improve mental health and well-being, particularly for young adults facing academic and transitional challenges. Overall, the findings highlight gratitude not only as a positive attitude but also as a crucial protective factor that can be leveraged to mitigate stress and enhance psychological well-being.